To study smoking violations through global positioning system-enabled mobile app, in Bhubaneswar, Odisha - Devi K Mishra; Nalini K Triathy; Bulu Mahanty; Bhupendra Buda; Manoj K Behera (Wolters Kluwer Medknow Publications, 2020)
Introduction: The Government of India has formulated the Cigarettes and Other Tobacco Products Act (COTPA) to implement measures to ensure that effective protection is provided to nonsmokers from involuntary exposure to tobacco smoke. Bhubaneswar is the capital city of Odisha, India, was declared as "Tobacco Smoke Free City" in 2010. For strengthening the implementation of the COTPA Act, an effective regular assessment is needed, and hence, an observational study was planned to assess the current violations of Tobacco Smoking in Bhubaneswar. Materials and Methods: In this observational study, 416 different places were chosen from four different zones of Bhubaneswar. Data were collected with the help of Mobile enabled global positioning system (GPS) technology and pretested structured questionnaire. Results: In this study, 52.88% places were found to be having smoking violations. The study shows maximum violations have occurred in public places (90.89%) followed by transit places (75%). Violations were found to be very low in government buildings, educational, medical institutes, and hotel/restaurants. The average number of smokers in the city was found to be 4.90/place and the average number of smokers was found to be 4.37/public place. Conclusion: In this study, GPS-enabled Mobile App can be used to identify the different locations, where a violation of law occurs. This may help administrators to properly plan and implement the law. Even though Bhubaneswar was declared "Tobacco Smoke free city" in 2010, it is still lacking behind in fulfilling the implementation of law, to reduce Second Hand Smoking.